Inflammation and Growth in Young Children with Obstructive Sleep Apnea Syndrome before and after Adenotonsillectomy - Nachalon, Yuval; Lowenthal, Neta; Greenberg-Dotan, Sari; Goldbart, Aviv D. (Mediators of Inflammation, 2014)
Background. Obstructive sleep apnea (OSA) is associated with growth impairment that usually improves following effective treatment. In this study we investigated the mechanisms underlying the growth processes in young children diagnosed with OSA, before and after adenotonsillectomy (T&A). Methods. Young children (6–36 months old) were enrolled and evaluated before and several months after T&A surgery for height, weight, circulating high sensitive C-reactive protein (CRP), and insulin-like growth factor 1 (IGF-1) levels. Caloric intake was assessed by a validated Short Food Frequency Questionnaire (SFFQ). Results. Following T&A, children added 4.81 cm and 1.88 kg to their height and weight, respectively (P<0.001 for both) and had a significant increase in BMI Z score (P=0.002). Increased caloric intake of 377 kcal/day was noted (P<0.001), with increased protein and decreased fat intake. The decrease in CRP levels correlated with the increase in body weight in boys (P<0.05, adjusted for caloric intake). Conclusions. Adenotonsillectomy results in enhanced somatic growth in young children that correlates with a decrease in systemic inflammation and caloric intake increment. Our findings imply that systemic inflammation may have an important role in this OSA-related morbidity.